Auditory rehabilitation in adults: results of a training program - Cristiane Bueno Sales; Luciana Macedo de Resende; Carlos Faria Santos Amaral (Revista CEFAC, 2019)
ABSTRACT Objective: to describe the findings of the auditory processing behavioral tests in patients with hearing loss before and after hearing aid fitting associated with auditory training. Methods: a descriptive analytical study that compared the findings of the auditory processing evaluation in 22 patients, from 19 to 62 years old, with mild or moderate sensorineural hearing loss. Tests used: Sound localization; Masking Level Difference; Alternate Disyllables Dichotic Listening Test; Melodic Frequency Pattern Test, Melodic Duration Pattern Test; Gaps in Noise; Speech in Noise Test. After the first tests, the patients were fitted with hearing aids and underwent eight auditory training sessions. The tests were retaken after a two-month period. Results: there was a predominance of females and a moderate degree hearing loss. In the comparison of the initial and final assessment situations, a statistically significant difference (p <0.05) was seen in all conditions studied, except for the Gaps in Noise and Masking Level Difference tests. Conclusion: the results have proven that the auditory training performed in adult users of hearing aids brought about significant improvements on the auditory processing skills, thus, modifying their auditory behavior. The improvement of the results of the auditory processing behavioral tests in the initial and final situations reflects the hearing functional improvement achieved.